Processo de inovação e seus reflexos na competitividade: um estudo nas indústrias do Cluster Calçadistas de Birigui SP - Vezozzo, Emiliana Camila Somaio Teixeira (2013)
This study tested the operation of the Process Innovation and Competitiveness Cluster inherent Footwear Birigui - SP. With a theoretical subsidized by theories and pre-existing knowledge - Theories of Competitive Advantage, Innovation and Cluster Theory - work made possible the analysis between the theories of innovation and competitiveness, fueled by the cluster environment, and the actions relevant to these themes practiced by the organizations that make up the cluster. The methodological approach of this study is characterized by Descriptive Research, with a census survey, whose universe characterized by cluster actors, providing information and analysis of quantitative and qualitative. The main results of the research pointed to effective cluster configuration footwear Birigui the perspective of the requirements mentioned by Porter (1993), demonstrated that the issue of innovation in the cluster occurs in all parameters of innovation highlighted by Schumpeter (1934); it was also realized that a large part of the competitive variables in the cluster environment, identified by Porter (1999) occur in the cluster under study